Algebra-Gleichungen-Exponentialgleichungen


  • $a b^{(cx+d)}+f=0 $
    1 2 3 4 5 6
    $a e^{(cx+d)}+f=0 $
    1 2 3 4

Beispiel Nr: 06
$ \text{Gegeben:}a b^{(cx+d)}+f=0 \\ \text{Basis: }b \\ \\ \text{Gesucht:} \text{Lösung der Gleichung} \\ \\ a b^{(cx+d)}+f=0 \\ \textbf{Gegeben:} \\ a=4 \qquad b=2 \qquad c=6 \qquad d=5 \qquad f=4 \\ \\ \textbf{Rechnung:} \\ 4 \cdot 2^{(6x+5)}+4 =0 \\ 4 \cdot 2^{(6x+5)}+4=0 \qquad /-4 \\ 4 \cdot 2^{(6x+5)}=-4 \qquad /:4 \\ 2^{(6x+5)}=-1 \qquad /\log_2 \\ -1 \leq 0 \rightarrow \text{keine Lösung}\\ $